2019
DOI: 10.21608/zumj.2019.10031.10980
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Calprotectin as a Serodiagnostic Marker for Neonatal Sepsis

Abstract: Background: Despite recent advances in neonatal care, sepsis remains a worldwide leading cause of morbidity, mortality and prolonged hospital stay in NICUs, so that the accurate and early diagnosis of neonatal sepsis is a relevant problem. Calprotectin is an antimicrobial, calcium and zinc binding heterocomplex protein that could be used as a nonspecific marker for activation of granulocytes and mononuclear phagocytes. Therefore, calprotectin has been proposed for the diagnosis of inflammatory conditions. Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 11 publications
3
9
1
Order By: Relevance
“…Respiratory instability was the most common manifestation seen in more than two thirds of cases (68%) in our study and was similar to the survey by Attia et al 15 In the current study, calprotectin levels did not significantly differ between males and females, which is consistent with other research. 15 , 23…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Respiratory instability was the most common manifestation seen in more than two thirds of cases (68%) in our study and was similar to the survey by Attia et al 15 In the current study, calprotectin levels did not significantly differ between males and females, which is consistent with other research. 15 , 23…”
Section: Discussionsupporting
confidence: 93%
“…Blood culture-positive cases contributed to 36.5% of the neonates in our research and are in line with the expected culture-positivity rates of 10 to 30% in neonatal sepsis. 24 Previous studies have documented blood culture-positive cases in 19.5% 14 , 16.6% 23 and 75% 15 cases. The most common isolates in the present study were Klebsiella and MRSA and were concurrent with the published literature.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Earlier studies have shown different cut-off levels, varying sensitivity, and specificity of serum calprotectin in detecting sepsis in neonates. [13][14][15][16] The literature on its diagnostic value in newborn sepsis in the Indian context is, however, scarce.…”
Section: Introductionmentioning
confidence: 99%